Voices of returning citizens: a qualitative study of a supportive housing program for ex-offenders in a rural community - Bownann, Edward L. (The prison journal, 2020)
Stable housing is a critical need for offenders at reentry and an urgent need for offenders returning to rural communities. Stable housing provides a foundation for life changes impacting recidivism and desistance. For rural jail populations, there are unique challenges in securing stable postrelease housing. In this qualitative study, we explore the impact of a supportive housing program through interviews with ex-offenders. The study examines how changes related to stable housing affect life course trajectories and transform social relationships. The research adds to the literature through narrative accounts of the importance of supportive housing for rural offender reentry.